MSI testing What's new? What should be considered? - Rueschoff, Josef; Baretton, Gustavo; Blaeker, Hendrik; Dietmaier, Wolfgang; Dietel, Manfred; Hartmann, Arndt; Horn, Lars-Christian; Joehrens, Korinna; Kirchner, Thomas; Knuechel, Ruth; Mayr, Doris; Merkelbach-Bruse, Sabine; et al. (Pathologe, 2021)
Based on new trial data regarding immune checkpoint inhibitors (ICIs), the detection of high-grade microsatellite instability (MSI-H) or underlying deficient mismatch repair protein (dMMR) is now becoming increasingly important for predicting treatment response. For the first time, a PD-1 ICI (pembrolizumab) has been approved by the European Medicines Agency (EMA) for first-line treatment of advanced (stage IV) dMMR/MSI-H colorectal cancer (CRC). Further indications, such as dMMR/MSI-H endometrial carcinoma (EC), have already succeeded (Dostarlimab, 2nd line treatment) and others are expected to follow before the end of 2021. The question of optimal testing in routine diagnostics should therefore be re-evaluated. Based on a consideration of the strengths and weaknesses of the widely available methods (immunohistochemistry and PCR), a test algorithm is proposed that allows quality assured, reliable, and cost-effective dMMR/MSI-H testing. For CRC and EC, testing is therefore already possible at the primary diagnosis stage, in line with international recommendations (NICE, NCCN). The clinician is therefore enabled from the outset to consider not only the predictive but also the prognostic and predispositional implications of such a test when counseling patients and formulating treatment recommendations. As a basis for quality assurance, participation in interlaboratory comparisons and continuous documentation of results (e.g., QuIP Monitor) are strongly recommended.
CRIS-Team WoS Importer:2021-09-17